(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
In this article, the essence of the term, the features of its formation are revealed on the example of the terms of the telephone communication network. Three methods of formation of telecommunication terms of special importance in the specific terminology of the Uzbek language were analyzed.